Hubungan Persepsi Kompensasi Dengan Kepuasan Kerja Karyawan Minimarket X di Sumatera Barat - Uthary Wulandari (Efisiensi: Jurnal Penelitian dan Pengembangan Ilmu Manajemen, 2024)
The study aims to examine the relationship between compensation perception and job satisfaction of minimarket x employees in West Sumatra. Data collection uses a scale of compensation perception and job satisfaction obtained by respondents. The analysis technique used is Spreamen-Rho with SPSS V26.0. The population and sample used are all minimarket x employees using the saturated sample method. The results of the hypothesis testing obtained a value of r = 0.885 and p = 0.000 (p < 0.05). The results prove that there is a relevant relationship between compensation perception and job satisfaction of minimarket x employees in West Sumatra.